FACTORS RELATED TO SMOKING BEHAVIOR IN HIGH SCHOOL ADOLESCENTS IN AL-HASRA IN 2022 - Azzahra, Karimah; Andriyani (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Background: Smoking behavior is widespread among teenagers and adults. This study examines factors associated with smoking behavior in adolescents at SMA AL-Hasra. Method: The research design used is a quantitative method with a cross-sectional approach with a sample of 123 respondents. The sampling technique used in this study is total sampling with the Chi-Square test to see a relationship. Result: The study showed that 43.1% f adolescents had smoking behavior. with the results of the P-Value statistical test p 0.000 in the knowledge category, p 0.003 in the attitude category, p 0.043 in the parental influence category, and p 0.000 in the influence category friend. Conclusion: It can be concluded that the analysis results show a significant relationship between respondents' knowledge , attitudes to respondents, the influence of respondents parents and the influence of peers a significant relationship on knowledge, attitudes, parental influence, and peer influence with smoking behavior in AL-Hasra Senior High school.